2021
DOI: 10.3389/fimmu.2021.666983
|View full text |Cite
|
Sign up to set email alerts
|

How to Train Your Dragon: Harnessing Gamma Delta T Cells Antiviral Functions and Trained Immunity in a Pandemic Era

Abstract: The emergence of viruses with pandemic potential such as the SARS-CoV-2 coronavirus causing COVID-19 poses a global health challenge. There is remarkable progress in vaccine technology in response to this threat, but their design often overlooks the innate arm of immunity. Gamma Delta (γδ) T cells are a subset of T cells with unique features that gives them a key role in the innate immune response to a variety of homeostatic alterations, from cancer to microbial infections. In the context of viral infection, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 255 publications
(256 reference statements)
3
29
0
Order By: Relevance
“…In addition to TLRs and TCRs gd T cells express other receptors, several of which are likely to be important in the recognition of viral infection, including NK type receptors (NKRs), DNAX Accessory Molecule 1 (DNAM1), and the Natural Cytotoxicity receptors (NCRs) NKp30, NK44 and NKp46. This review focuses on the NKR natural killer group 2-member D (NKG2D) only, as other NKRs have been recently reviewed by Caron et al (69). NKG2D is an activating C-type lectin originally found on Natural Killer cells, but also highly expressed on both Vd1 and Vd2 T cells.…”
Section: Gd T Cell Recognition Of Viral Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to TLRs and TCRs gd T cells express other receptors, several of which are likely to be important in the recognition of viral infection, including NK type receptors (NKRs), DNAX Accessory Molecule 1 (DNAM1), and the Natural Cytotoxicity receptors (NCRs) NKp30, NK44 and NKp46. This review focuses on the NKR natural killer group 2-member D (NKG2D) only, as other NKRs have been recently reviewed by Caron et al (69). NKG2D is an activating C-type lectin originally found on Natural Killer cells, but also highly expressed on both Vd1 and Vd2 T cells.…”
Section: Gd T Cell Recognition Of Viral Infectionmentioning
confidence: 99%
“…γδ T cells are involved in the first line of defense to a number of diseases, including cancer, bacterial infections, and viral infections. Studies have demonstrated their rapid activation and cytotoxicity to various viruses, including cytomegalovirus (CMV) ( 52 , 53 ), influenza A virus ( 54 56 ), human immunodeficiency virus (HIV) ( 57 59 ), hepatitis B and C viruses (HBV and HCV) ( 60 62 ), Epstein Bar Virus (EBV) ( 63 ) and severe acute respiratory syndrome (SARS) virus ( 64 ), as reviewed by others ( 50 , 51 , 65 69 ). Additionally, γδ TCR knockout mice show an increase in viral titer or reduced survival when infected with West Nile virus or vaccinia virus ( 70 , 71 ).…”
Section: Gamma Delta T Cellsmentioning
confidence: 99%
See 3 more Smart Citations